Case Report: Double chimney in valve-in-valve procedures for high-risk coronary obstruction - Selma T. Cook; Mario Togni; Stéphane Cook (Frontiers in Cardiovascular Medicine, 2023)
The chimney technique has been utilized to minimize the risk of coronary artery obstruction during valve-in-valve procedures. Here, we present a case involving an 89-year-old female patient with low coronary ostia, severe aortic regurgitation, and intractable heart decompensation caused by degenerated aortic bioprosthesis. The patient underwent a successful transcatheter aortic valve implantation procedure using the chimney technique in both coronary ostia.